Reliability-Based Structural Optimization Accounting for Manufacturing and Material Quality - Doliński, K.; Stocki, R. (Engineering Transactions, 2001)
The reliability-based optimization problem in which the structural material and manufacturing quality is assumed to be uncertain is considered. Moreover, the quality cost is appropriately taken into consideration in the formula determining the total cost of the structure. Some parameters describing the quality, namely the means and variances of the material properties and the variances of the precision of assembling of the structure are considered as the design parameters in the optimization procedure, in which the required structural reliability level determines some constrains to be satisfied in searching for the minimum structural cost.